Solid Waste Engineering and Management Volume 2 - Wang, Lawrence K.; Wang, Mu-Hao Sung.; Hung, Yung-Tse.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is the second volume in a three-volume set on Solid Waste Engineering and Management. It focuses on sustainability, single waste stream processing, material recovery, plastic waste, marine litter, sludge disposal, restaurant waste recycling, sanitary landfills, landfill leachate collection, and landfill aftercare as it pertains to solid waste management. The volumes comprehensively discuss various contemporary issues associated with solid waste pollution management, impacts on the environment and vulnerable human populations, and solutions to these problems. .
Chapter 1-Sustainable solid waste management -- Chapter 2-Single waste stream processing and Material Recovery Facility (MRF) -- Chapter 3-Construction and Demolition (C&D) waste management and disposal -- Chapter 4-Recovery of plastic waste -- Chapter 5-Solid waste and marine litter management -- Chapter 6-Sewage sludge waste disposal -- Chapter 7-Restaurant waste recycle and disposal -- Chapter 8-Sanitary Landfill type & design -- Chapter 9-Landfill Leachate Collection and Characteristics -- Chapter 10-Landfill aftercare management plan.
Keywords: Environment; Refuse and refuse disposal; Environmental engineering; Biotechnology; Bioremediation; Environmental Sciences; Waste Management/Waste Technology; Environmental Engineering/Biotechnology.; Refuse and refuse disposal